2023
DOI: 10.1161/jaha.123.029518
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Tortuosity Is Associated With Increased Rate of Cardiovascular Events in Vascular Ehlers‐Danlos Syndrome

Sara B. Stephens,
Sherene Shalhub,
Nicholas Dodd
et al.

Abstract: Background Arterial tortuosity is associated with adverse events in Marfan and Loeys‐Dietz syndromes but remains understudied in Vascular Ehlers‐Danlos syndrome. Methods and Results Subjects with a pathogenic COL3A1 variant diagnosed at age <50 years were included from 2 institutions and the GenTAC Registry (National Registry of Genetically Triggered Thoracic Aortic Aneurysms and Cardiovascular Conditions). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Stephens et al developed a height‐adjusted vertebral tortuosity index and found an association between height‐adjusted vertebral tortuosity index and the occurrence of a cardiovascular event before 30 years of age (area under the curve=0.71). 10 In multivariate analysis, they found that older age was the only factor associated with increased cardiovascular event rate, whereas height‐adjusted vertebral tortuosity index was not; however, height‐adjusted vertebral tortuosity index was associated with events among those with high‐risk variants <40 years of age, suggesting effect modification by genotype and age. 10 It also suggests that the effect of height is only significant in patients <40 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Stephens et al developed a height‐adjusted vertebral tortuosity index and found an association between height‐adjusted vertebral tortuosity index and the occurrence of a cardiovascular event before 30 years of age (area under the curve=0.71). 10 In multivariate analysis, they found that older age was the only factor associated with increased cardiovascular event rate, whereas height‐adjusted vertebral tortuosity index was not; however, height‐adjusted vertebral tortuosity index was associated with events among those with high‐risk variants <40 years of age, suggesting effect modification by genotype and age. 10 It also suggests that the effect of height is only significant in patients <40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In multivariate analysis, they found that older age was the only factor associated with increased cardiovascular event rate, whereas height‐adjusted vertebral tortuosity index was not; however, height‐adjusted vertebral tortuosity index was associated with events among those with high‐risk variants <40 years of age, suggesting effect modification by genotype and age. 10 It also suggests that the effect of height is only significant in patients <40 years of age. These inconsistent findings may, in part, be related to the use of TI as a measure of arterial tortuosity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations